Isolation and identification of proteolytic lactic acid bacteria from freshwater pomfret (Colossoma macropomum) intestine - Risti Wulaningtyas; Rudiana Agustini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The production of freshwater pomfret (Colossoma macropomum) in Indonesia is abundant, but the digestive tract waste weighing 10-15% of the fish body is not widely utilized. The fish's digestive tract can potentially produce lactic acid bacteria (LAB). Lactic acid bacteria have a proteolytic system that can produce extracellular protease enzymes. Protease enzymes are the most widely utilized enzymes in various industries and have a global revenue of up to 2.1 billion in 2021. Protease enzymes derived from microbes are in great demand due to the efficiency of time, place, cost, and better cultivation techniques than animal and plant sources. This study aimed to isolate and identify proteolytic lactic acid bacteria from the intestines of freshwater pomfret fish and determine their proteolytic index. The methods used were morphological, biochemical, sugar, and proteolytic tests. The BAT-A isolate with the highest proteolytic index of 2.52 with characteristics of Gram-positive, non-spore, facultatively anaerobic, catalase-negative, non-motile, homofermentative, can ferment glucose, maltose, lactose and sucrose which were then identified as proteolytic lactic acid bacteria Enterococcus sp which has the potential as a candidate source of protease enzymes from bacteria isolated from the intestines of freshwater pomfret.